Do grazing intensity and herbivore type affect soil health? Insights from a semi‐arid productivity gradient. Issue 3 (1st December 2016) - Eldridge, David J.; Delgado‐Baquerizo, Manuel; Travers, Samantha K.; Val, James; Oliver, Ian
Summary: Grazing is one of the most widespread forms of intensive management on Earth and is linked to reductions in soil health. However, little is known about the relative influence of herbivore type, herbivore intensity and site productivity on soil health. This lack of knowledge reduces our capacity to manage landscapes where grazing is a major land use. We used structural equation modelling to assess the effects of recent (cattle, sheep, goats, kangaroos and rabbit dung) and historic (cattle, sheep/goat livestock tracks) herbivore activity on soil health at 451 sites across 0·5 M km 2 of eastern Australia. We assessed the direct and indirect effects of increasing herbivore intensity, using dung and livestock tracks, on 15 morphological, physical and chemical attributes that are indicative of soil health, and we used these attributes to derive three indices representing the capacity of the soil to maintain its structural integrity (stability), cycle nutrients (nutrients) and maintain water flow (infiltration). Grazing had negative effects on the three soil health indices, but these effects varied with productivity. Grazing intensity was associated with strong reductions in the stability and nutrient indices under low productivity, but these effects diminished with increasing productivity. Herbivore effects on individual attributes varied in relation to productivity level and were strongly herbivore specific, with most due to cattle grazing, and to a lesser extent, sheep, goats and rabbits. Few effects due to kangaroos or historic grazing by livestock were observed. Synthesis and applications . Our study shows that livestock and rabbits degrade soil health through grazing, and its effects are strongest under low or moderate productivity; however, kangaroo effects are benign. Our findings support calls for resource management agencies to consider site productivity, as well as herbivore type and intensity, when developing strategies to manage grazing by livestock, and feral and native herbivores. Abstract : Our study shows that livestock and rabbits degrade soil health through grazing, and its effects are strongest under low or moderate productivity; however, kangaroo effects are benign. Our findings support calls for resource management agencies to consider site productivity, as well as herbivore type and intensity, when developing strategies to manage grazing by livestock, and feral and native herbivores.